Development of flat sheet thin film composite nanofiltration membrane for separation of acetic acid inhibitor and sugar from biomass hydrolysate - Siti Normunira, Ramli (2019)
Effective separation process is required in processing biomass hydrolysate to recover xylose and glucose for further fermentation stage and to remove undesired inhibitor such as acetic acid. The conventional separation methods such as evaporation, chromatography and heating are complicated, involve long processing time and extensive loss of the fermentable sugar. Thus, thin film composite (TFC) nanofiltration (NF) was chosen as biorefinery separation process due to its technical and economic advantages. The effect of the support membrane on the TFC performance was investigated in this study as the support membrane influence the performance of TFC membrane. Four different types of the polyethersulfone (PES) support was prepared by varying the PES concentration in dope solution from 17 wt.% PES to 23 wt.% PES. TFC membrane was prepared by performing interfacial polymerization (IP) on the support membrane to form an active thin film separation layer. TFC membrane was prepared by using 0.2 % w/v piperazine (PIP) and 0.2 % w/v tri-mesoyl chloride monomers (TMC). TFC membrane prepared from 23 wt.% PES support membrane showed the higher separation factor. The separation factor for xylose/glucose, acetic acid/glucose and acetic acid/xylose were 1.450.06, 1.860.05 and 1.290.09, respectively. Next, the effects of monomer type and parameters during IP were investigated for acetic acid removal and xylose/glucose separation. Using the best support membrane which is PES 23, three different types of monomers in IP process was studied which are PIP, m-phenylene diamine (MPD) and triethanolamine (TEOA). PIP TFC membrane showed the highest water flux of xylose (4.80.97 L/m 2 .h), glucose (5.480.00 L/m 2 .h) and acetic acid (5.820.48 L/m 2 .h). The separation factor for the PIP TFC membrane was the best among the monomer tested which are 1.450.06, 1.860.05 and 1.290.09 for xylose/glucose, acetic acid/glucose and acetic acid/xylose, respectively. The separation factor for MPD TFC membrane was 0.900.07, 0.740.11 and 0.830.18 for xylose/glucose, acetic acid/glucose and acetic acid/xylose, respectively. Meanwhile, the separation factor for TEOA TFC membrane was 0.940.12, 1.120.11 and 1.210.27 for xylose/glucose, acetic acid/glucose and acetic acid/xylos e, respectively. The effect of PIP monomer concentration (0.15 – 3.0 % w/v) and aqueous solution reaction time (45 second – 15 minutes) was studied. 2.0 % w/v of PIP and 2 minutes of aqueous solution reaction time were selected as the best condition to prepare the PIP TFC membrane with separation factor of 1.060.23, 1.590.39 and 1.640.05 for xylose/glucose, acetic acid/glucose and acetic acid/xylose, respectively. By using 23 wt.% PES concentration as a support to 2.0 % w/v of PIP at 2 minutes reaction time in aqueous solution TFC NF membrane ascertained that TFC NF membrane produced in this study showed a potential for the application in biorefinery.